RESEARCHING ECOLOGICAL VARIABILITY OF AGRONOMIC TRAITS IN POTATO VARIETIES WHEN THEY ARE INTRODUCED INTO SEVERE ENVIRONMENTS OF THE ALTAI MOUNTAINS - T. A. Streltsova; A. A. Opleukhin; N. A. Okasheva (Труды по прикладной ботанике, генетике и селекции)
This article analyzes the data of researching ecological variability of important agronomic traits in potato varieties introduced under the severe climate conditions of the Altai Mountains after several years of environmental variety trials in different altitudinal zones of the Altai Republic. The trials were performed for 31 potato cultivars of various maturity groups. They made it possible to identify varieties most suitable for cultivation in the areas of testing, with high levels of productivity and stable manifestation of this trait under different weather conditions. The analysis was based on the methods suitable for assessing the interaction between factors and all the traits, with consequent evaluation of variations in individual traits under different environmental factors.